Küzdelem az egységes közép-európai gazdaságért : Hantos Elemér : 1881-1942 - Szávai, Ferenc (Közép-Európai Közlemények, 2016)
Economic unity and modernization have ended with the dissolution of the Austro-Hungarian Monarchy. New nation states, independent economies have emerged in its place. The peace treaties allowed economic and commercial cooperation between successor states, and several Central European conceptions have been conceived, but without any real significant collaboration. One of them was the Little-Central European conception of Elemér Hantos about the economic reorganization of Central Europe. Elemér Hantos was the precursor of the idea of peaceful coexistence and ways to achieve it, not just in Central Europe but in whole of Europe: emphasizing what unites us and not what separates us.